Islam dalam Dinamika Sosial Sunda - Sukron Kamil (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2007)
Unlike the pattern of Islamic society in Java, which has long been the focus of study, the pattern of Islam in Sunda seems to receive less serious attention. Writing motivated by this reason, among others, found that the Sundanese community in general can be divided into two parts: Priangan and Pakulonan. In terms of Islam, they can be divided into three parts, as Geertz categorizes Javanese society: Santri, Abangan, and Priayi. The Santri segment of Sundanese society is divided into two parts: traditional Muslims and Orthodox or modernist. Generally, syncretism is one of the characteristics of the majority of Sundanese Islam. Even in Sundanese society, there are pre-Islamic religions that have survived to this day, although some are influenced by Islam in certain aspects, such as